Differential patterns of Fos induction in the hypothalamus of the rat following central injections of galanin-like peptide and galanin - Clifton, Donald K.; Baumgartner, James W.; Steiner, Robert A.; Fraley, Gregory S.; Shimada, Issei (Endocrine Society, 2003)
Galanin and its newly discovered relative galanin-like peptide (GALP) are neuropeptides that are implicated in the neuroendocrine regulation of body weight and reproduction. GALP has been shown to bind in vitro to galanin receptor subtypes 1 and 2, but whether it has its own specific receptor(s) is unknown. We reasoned that if GALP acts through a receptor that is distinct from galanin receptors, then GALP should activate central pathways that are different from those activated by galanin. The purpose of this study was to determine whether galanin and GALP produce different patterns of neuronal activation within the hypothalamus. Quantitative analysis of Fos immunoreactivity showed that galanin induced a significantly greater number of Fos-positive nuclei in the paraventricular nucleus compared with GALP (P < 0.001); however, compared with galanin, GALP induced significantly more Fos-positive cells in the horizontal limb of the diagonal band of Broca, caudal preoptic area, arcuate nucleus, and median eminence (P < 0.05). These observations suggest that GALP and galanin act through different receptor-mediated pathways to exert their effects on the regulation of body weight and reproduction and identify target cells for GALP's specific actions in the hypothalamus, including the preoptic area, paraventricular and arcuate nuclei, and the median eminence.
Keywords: Fos induction; hypothalamus; galanin-like peptide; rat; galanin; Injections, Intraventricular; Hypothalamus, drug effects, metabolism; Nerve Tissue Proteins, pharmacology; Preoptic Area, drug effects, metabolism; Male; Cerebrospinal Fluid; Research Support, U.S. Gov't, Non-P.H.S.; Proto-Oncogene Proteins c-fos, biosynthesis; Rats; Paraventricular Hypothalamic Nucleus, drug effects, metabolism; Galanin, pharmacology; Galanin-Like Peptide; Feeding Behavior, drug effects; Rats, Sprague-Dawley; Animals; Arcuate Nucleus, drug effects, metabolism; Research Support, U.S. Gov't, P.H.S.